An estimate of the incidence and prevalence of laryngeal papillomatosis in Sao Paulo State (Brasil) - Mercuri, Gustavo [UNESP]; Rodrigues, Sergio Augusto [UNESP]; Garcia Martins, Regina Helena [UNESP] (Assoc Medica Brasileira, 2020)
BACKGROUND: Recurrent laryngeal papillomatosis, caused by the Human Papilloma Virus, has a significant economic impact worldwide and there are no epidemiological data of this disease in Brasil. OBJECTIVE: The objective of the study was to estimate the incidence and prevalence of laryngeal papillomatosis of some otorhinolaryngology centers in Sao Paulo State (Brasil). METHODS: A questionnaire containing data on the number of new and follow-up cases diagnosed with laryngeal papillomatosis was sent to the Otorhinolaryngology services (n=35) of Sao Paulo State (Brasil). RESULTS: A total of 20 otorhinolaryngology centers answered the questionnaire. Of these, the five largest regional health centers were selected as follows: Campinas (42 cities - 4,536,657 inhabitants), Sao Jose do Rio Preto (102 cities - 1,602,845 inhabitants), Ribeirao Preto (26 cities -1,483,715 inhabitants), Bauru (68 cities - 1,770,427 inhabitants), and Sorocaba (47 cities - 2,478,208 inhabitants). The incidence and prevalence of each regional health centers were, respectively: Campinas (5.51;7.27), Sorocaba (2.02;6.86), Sao Jose do Rio Preto (1.87;749), Ribeirao Preto (11.46;22.92), and Bauru (3.95;7.91). CONCLUSION: The incidence and prevalence of the laryngeal papillomatosis of the five largest regional health centers of the interior of Sao Paulo State (Brasil) varied between 1.87 to 11.46 and 6.86 to 22.92 per 1,000,000 inhabitants, respectively for a total population of 11,871,852 inhabitants.
Keywords: Papilloma; Larynx; Laryngeal neoplasms; Papillomaviridae; Epidemiology; Incidence; Prevalence